Individualised nutritional support in medical inpatients at nutritional risk: a randomised clinical trial. Issue 10188 (8th June 2019) - Schuetz, Philipp; Fehr, Rebecca; Baechli, Valerie; Geiser, Martina; Deiss, Manuela; Gomes, Filomena; Kutz, Alexander; Tribolet, Pascal; Bregenzer, Thomas; Braun, Nina; Hoess, Claus; Pavlicek, Vojtech; et al.
Summary: Background: Guidelines recommend the use of nutritional support during hospital stays for medical patients (patients not critically ill and not undergoing surgical procedures) at risk of malnutrition. However, the supporting evidence for this recommendation is insufficient, and there is growing concern about the possible negative effects of nutritional therapy during acute illness on recovery and clinical outcomes. Our aim was thus to test the hypothesis that protocol-guided individualised nutritional support to reach protein and caloric goals reduces the risk of adverse clinical outcomes in medical inpatients at nutritional risk. Methods: The Effect of early nutritional support on Frailty, Functional Outcomes, and Recovery of malnourished medical inpatients Trial (EFFORT) is a pragmatic, investigator-initiated, open-label, multicentre study. We recruited medical patients at nutritional risk (nutritional risk screening 2002 [NRS 2002] score ≥3 points) and with an expected length of hospital stay of more than 4 days from eight Swiss hospitals. These participants were randomly assigned (1:1) to receive either protocol-guided individualised nutritional support to reach protein and caloric goals (intervention group) or standard hospital food (control group). Randomisation was done with variable block sizes and stratification according to study site and severity of malnutrition using an interactive web-response system. In the intervention group, individualised nutritional support goals were defined by specialist dietitians and nutritional support was initiated no later than 48 h after admission. Patients in the control group received no dietary consultation. The composite primary endpoint was any adverse clinical outcome defined as all-cause mortality, admission to intensive care, non-elective hospital readmission, major complications, and decline in functional status at 30 days, and it was measured in all randomised patients who completed the trial. This trial is registered withClinicalTrials.gov, numberNCT02517476 . Findings: 5015 patients were screened, and 2088 were recruited and monitored between April 1, 2014, and Feb 28, 2018. 1050 patients were assigned to the intervention group and 1038 to the control group. 60 patients withdrew consent during the course of the trial (35 in the intervention group and 25 in the control group). During the hospital stay, caloric goals were reached in 800 (79%) and protein goals in 770 (76%) of 1015 patients in the intervention group. By 30 days, 232 (23%) patients in the intervention group experienced an adverse clinical outcome, compared with 272 (27%) of 1013 patients in the control group (adjusted odds ratio [OR] 0·79 [95% CI 0·64–0·97], p=0·023). By day 30, 73 [7%] patients had died in the intervention group compared with 100 [10%] patients in the control group (adjusted OR 0·65 [0·47–0·91], p=0·011). There was no difference in the proportion of patients who experienced side-effects from nutritional support between the intervention and the control group (162 [16%] vs 145 [14%], adjusted OR 1·16 [0·90–1·51], p=0·26). Interpretation: In medical inpatients at nutritional risk, the use of individualised nutritional support during the hospital stay improved important clinical outcomes, including survival, compared with standard hospital food. These findings strongly support the concept of systematically screening medical inpatients on hospital admission regarding nutritional risk, independent of their medical condition, followed by a nutritional assessment and introduction of individualised nutritional support in patients at risk. Funding: The Swiss National Science Foundation and the Research Council of the Kantonsspital Aarau, Switzerland.